1980
DOI: 10.1159/000162970
|View full text |Cite
|
Sign up to set email alerts
|

A Cytofluorometric Analysis of Polymer-Induced Mast Cell Secretion

Abstract: Quantitative cytofluorometry was used to study the mechanism of mast cell secretion induced by polymyxin B in vitro. We measured 5-hydroxytryptamine (5-HT) and heparin in mast cells and individual mast cell granules, extruded from the cells or obtained from the interior of the cells by micromanipulation. Mast cell granules of untreated control cells contained both 5-HT and heparin. After polymyxin stimulation both intracellular and extruded mast cell granules contained heparin, but some intracellular and all e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1

Year Published

1980
1980
1984
1984

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 16 publications
3
21
1
Order By: Relevance
“…In a recent investigation we used these methods for quantitation of polymyxin-in duced mast cell secretion of 5-HT and hep arin from mast cells and individual mast cell granules [17]. We found that heparin was not released from individual granules.…”
Section: Introductionmentioning
confidence: 90%
“…In a recent investigation we used these methods for quantitation of polymyxin-in duced mast cell secretion of 5-HT and hep arin from mast cells and individual mast cell granules [17]. We found that heparin was not released from individual granules.…”
Section: Introductionmentioning
confidence: 90%
“…Measurement of the heparin content of individual granules extruded from mast cells as a result of a secretory process or obtained from the inte rior of the cell by micromanipulation produced no evidence for release of heparin from the granular ma trix [Gustavsson and Enerback, 1980]. Release of he parin can therefore be taken as a direct measure of re lease of granules.…”
Section: Discussionmentioning
confidence: 94%
“…1972a;Andersson et al, 1973;Gustavsson and Enerback, 1980], Granules in contact with the extracellular environment, wheth er retained in the cell or not, have an altered morphol ogy probably related to amine release [Bloom and Haegermark, 1965;Lagunoff 1973;Andersson and Uvnas, 1975]. It is still unsettled whether selective amine release can take place without accompanying exocytosis of granules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations